A 3 year post‐intervention follow‐up on mortality in advanced heart failure (EVITA vitamin D supplementation trial). (11th September 2020) - Zittermann, Armin; Ernst, Jana B.; Prokop, Sylvana; Fuchs, Uwe; Berthold, Heiner K.; Gouni‐Berthold, Ioanna; Gummert, Jan F.; Pilz, Stefan
Abstract: Aims: Vitamin D supplementation is widely used in the clinical setting, but its effects on mortality and cardiovascular outcomes in patients with heart failure are unclear. This paper reports outcome data that were collected during follow‐up of 3 years after closure of the EVITA trial (a 3 year randomized, placebo‐controlled, intervention study with 4000 IU vitamin D daily in patients with advanced heart failure), to capture potential latency effects of vitamin D supplementation on clinical outcomes. Methods and results: The prespecified primary endpoint was overall mortality. Secondary endpoints included hospitalization, mechanical circulatory support implantation, high urgent listing for heart transplantation, and heart transplantation. For group comparisons, we used Cox regression models with a time‐dependent categorical covariate. The calculated net difference in circulating 25‐hydroxyvitamin D between the vitamin D and placebo groups dropped from 60.9 nmol/L at the end of the active study period to 3.2 nmol/L at the end of the post‐intervention period. During the entire 6 year period, 73 patients (36.5%) died in the placebo group and 76 (38.8%) in the vitamin D group. Out of these 149 patients, 36 and 39 died during the first 3 years, and 37 and 37 during the second 3 years, respectively. The hazard ratio (HR) for mortality in the vitamin D versus the placebo group was 1.06 [95% confidence interval (CI): 0.68–1.66] for the first 3 years and 1.07 (95% CI: 0.68–1.70) for the 3 year post‐intervention follow‐up. Compared with the placebo group, the HRs for hospitalization and for mechanical circulatory support implant were significantly higher in the vitamin D group during vitamin D supplementation (HR = 1.31, 95% CI: 1.01–1.68 and HR = 2.01, 95% CI: 1.08–3.76, respectively) but not after vitamin D discontinuation (HR = 1.10, 95% CI: 0.62–1.94 and HR = 0.99, 95% CI: 0.38–2.56, respectively). There was no significant time‐dependent effect on the risk of high urgent listing for heart transplantation and heart transplantation. Conclusions: No beneficial latency effects of vitamin D supplementation on overall mortality could be demonstrated. Instead, the disappearance of unfavourable findings in the vitamin D group (higher HRs for hospitalization and for mechanical circulatory support implant) after vitamin D discontinuation supports the assumption of adverse vitamin D effects on the cardiovascular system at doses of 4000 IU daily.